Artificial Intelligence's Challenges and Opportunities for Management Education: A Journey of AI in Nonlinear Sciences - Shah, Binod; Sah, Rajesh Kumar; Sah, Kiran Kumari; Sahani, Suresh Kumar (EDUMALSYS Journal of Research in Education Management, 2024)
This study explores the problems and prospects of integrating Artificial Intelligence (AI) in management education, a field that has significantly evolved with technological advancements. AI has the potential to revolutionize management education by enhancing personalized learning, improving administrative efficiency, and providing data-driven decision-making support. However, challenges such as the digital divide, resistance to change among educators, data privacy concerns, and the substantial investments required for technology and training impede its widespread adoption. A mixed-methods approach, combining a literature review and survey, was employed to gather perspectives from the participants, including educators, administrators, and students. The findings reveal that while a major of institutions use AI for management education, significant concerns remain regarding data privacy, algorithmic bias, and the cost of implementation. The study underscores the need for comprehensive training, ethical guidselines, and increased funding to overcome these barriers. By addressing these challenges, management education institutions can effectively leverage AI to enhance learning outcomes, administrative efficiency, and overall educational quality. The paper provides valuable insights for educators, administrators, and policymakers aiming to integrate AI into management education, ensuring a smoother transition and greater acceptance among stakeholders.